Relatório de Estágio Profissional "Reinterpretação da Identidade Pessoal e Profissional" - Rita Pereira Rodrigues (2017)
The current work was elaborated within the context of professional internship included in the Master's degree in Teaching Physical Education in Basic and Secondary Education of Faculty of Sport of University of Porto (FADEUP). The professional internship was in Rio Tinto EB 2,3 school, in the internship nuclei, composed of two trainee students, supervised by the school cooperating teacher and the professor of the faculty. In this report, my professional growth is fully portrayed throughout this year. Thus, the report reveals the subjective plan with my opinion, as well as the interface between objective view of the remaining methodologies in the literature and those chosen for my evaluation. This work is divided into five chapters: the "Introduction", which refers the contextualization of the pertinence of this document also the definition of some concepts supported in the state of art; "Personal Framework", here I will try to convey the reasons that led me to choose the teaching and sports area, based on a constant process between past and present; and "Performance of the Professional Practice" that is divided into three areas. Area of management and organization of teaching and learning, that are include the four central components of a teacher's cycle of action: the conception, planning, realization and evaluation of the teaching process; the area of School Participation and Community Relations, where is the reflection of all activities that I was involved; and the Professional Development area, with the research study realized during the year. The present study came from a worldwide problematic which is difficult to control, so obesity. Therefore, this study is related to the increase the percentage values of obesity and an adoption of unhealthy habits, such as physical inactivity. To conclude, praising the panoply of moments and learning that helped to build my professional identity as a future teacher of physical education.